Movie Migrations : Transnational Genre Flows and South Korean Cinema - Chung, Hye Seung, 1971-; Diffrient, David Scott, 1972- (Book collections on Project MUSE., 2015)
This timely new study reveals that, though South Korean popular culture might be enjoying new prominence on the global stage, the nation's film industry has long been a hub for creative appropriations across national borders. Movie Migrations explores how Korean filmmakers have put a unique spin on familiar genres, while influencing world cinema from Hollywood to Bollywood.